Hubungan kualitas pelayanan perawat dengan kepuasan pasien diabetes melitus type II - hany pratiwi (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2020)
ABSTRACT Patient satisfaction is an indicator of service success that affects satisfaction in nursing services. If the service is approprite to expectations, the quality of service is considered good and satisfying, otherwise the service received is not satisfactory, the quality of service is as poor. The 5 dimensions of patient satisfaction are tangibles, reliability, responsiveness, assurance, and empathy. The purpose of this research was to determine the relationship of tangibles, reliability, responsiveness, assurance and empathy with the satisfaction of type 2 diabetes mellitus patients in Citra Medika 2 Clinic, Medan City. The type of research used associative research, that aims to determine the effect or also the relationship between two or more variables. This research is quantitative, with a cross sectional design which is a research design by examining the relationship between two variables in a situation or group of subjects. The population of this research were all patients with Diabetes Mellitus Type 2 in Citra Medika 2 Clinic, Medan City, totaling 1,524 people. The sample of 86 people was obtained using the Purposive Sampling technique, the research instrument used questionnaire.The results obtained that variables that related to patient satisfaction with Diabetes Mellitus Type 2, are tangibles (p value = 0,000), assurance (p value = 0.004), Empathy (p value = 0.006). It is recommended to Citra Medika 2 Clinic especially nurses to maintain good service quality and continue to improve the quality of service to patients.